The challenges of governance in a complex world - Ho, Peter 1968- (Singapore World Scientific Publishing Co., 2018)
The Challenges of Governance in a Complex World collects the four IPS-Nathan Lectures that Mr Peter Ho, the Institute of Policy Studies’ third S R Nathan Fellow for the Study of Singapore delivered between April and May 2017, and includes highlights of his dialogue with the audience.
Foreword -- About the Moderators -- Lecture I Hunting Black Swans and Taming Black Elephants: Governance in a Complex World -- Q&A Session, Moderator: Debra Soon -- Lecture II Governing in the Anthropocene: Risk & Resilience, Imagination & Innovation -- Q&A Session, Moderator: Chan Heng Chee -- Lecture III The Paradox of Singapore and the Dialectic of Governance -- Q&A Session, Moderator: Chng Kai Fong -- Lecture IV The Future: Governance, Unintended Consequences and the Redemption of Hope -- Q&A Session, Moderator: Chua Mui Hoong -- Bibliography
Includes bibliographical references.
Keywords: Political planning -- Singapore; Complexity (Philosophy); Resilience (Personality trait); Technological innovations -- Singapore